Предмет: Алгебра,
автор: настя40841
решить уравнение (2x-3)^3-8x^2 (-x-9)=9(4x^2+3)
Ответы
Автор ответа:
0
6х-9-16х(в квадрате)-18=72х+27
6х-16х(в квадрате)-72=27+9+18
6х-16х(в квадрате)-72=27+9+18
Автор ответа:
0
ответ какой?
Автор ответа:
0
Сейчас скажу, подожди минутку
Автор ответа:
0
ок
Автор ответа:
0
-1,2 и 1,2. Там через дискриминант решается.
Автор ответа:
0
спс
Похожие вопросы
Предмет: Биология,
автор: superbobr3
Предмет: Русский язык,
автор: asakipop
Предмет: История,
автор: jdhfjffjdjfhfdkf
Предмет: Химия,
автор: Merem1Philonuk